2018
DOI: 10.4025/actascibiolsci.v40i1.42562
|View full text |Cite
|
Sign up to set email alerts
|

<b>Does riparian vegetation affect fish assemblage? A longitudinal gradient analysis in three Amazonian streams

Abstract: The degradation of riparian vegetation in low-order streams can cause irreversible environmental damage, biodiversity loss and alter the structure of communities. In this context, the present study evaluated how the level of degradation of riparian vegetation influences the fish assemblage in three low-order streams in the Brazilian Amazon. In each stream, three different stretches were delimited, distributed in the environments of forest, edge and pasture, and the samplings were conducted in three hydrologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 45 publications
0
5
1
1
Order By: Relevance
“…and Virgilio et al (2018). Although Carnegiella strigata was found in anthropized environments in the present study, we also found it as an indicator of the preserved areas due to the great abundance of individuals in these streams.…”
Section: The Present Study Found Evidence Thatcontrasting
confidence: 40%
“…and Virgilio et al (2018). Although Carnegiella strigata was found in anthropized environments in the present study, we also found it as an indicator of the preserved areas due to the great abundance of individuals in these streams.…”
Section: The Present Study Found Evidence Thatcontrasting
confidence: 40%
“…Porém é comparável com os resultados de inventários em pequenos igarapés em outras microbacias amazônicas em condições semelhantes de redução da cobertura florestal ciliar. Entre esses: microbacias da Amazônia Central (23 espécies - Beltrão et al, 2018), Meridional (39 espécies -Santos et al, 2017, Ocidental (32 espécies - Virgílio et al, 2018) e Oriental (29 espécies - Ilha et al, 2019).…”
Section: Discussionunclassified
“…The Acre river is a medium-sized watercourse, by the standards of the Amazon basin, running 1190 km from its source, in Peru, to its confluence with the Purus river in the Brazilian state of Amazonas, first passing through Bolivia and then the state of Acre, Brazil. Ichthyological research in Acre has included studies on the Juruá river (Silvano et al 2001) and the middle Purus (Dos Anjos et al 2008), as well as studies of the streams (Claro-García et al 2013, Corrêa et al 2018, Virgilio et al 2018, 2019 and lakes (da Silva et al 2013) of the Acre basin.…”
Section: Introductionmentioning
confidence: 99%